Observing Two Reading Intervention Programs for Students with Dyslexia. Issue 2 (15th March 2022) - Hall, Colby; Dahl-Leonard, Katlynn; Cannon, Grace
ABSTRACT: This exploratory study examined the nature of instruction provided in two reading intervention programs designed for elementary-grade students with dyslexia (The Multisensory Teaching Approach and Reading RULES!). In addition to documenting the proportion of time dedicated to particular content components (i.e., letter-name knowledge, phonological awareness, phonics/decoding, encoding, sight word recognition, passage reading/fluency, comprehension, vocabulary), the research team also documented the degree to which instruction (a) included teacher explanation/modeling, guided practice, group practice, and individual practice, (b) addressed particular types of decoding/encoding procedures, including multi-sensory (defined as tactile/kinesthetic) procedures and use of orthographic rules, and (c) made use of given instructional materials. The team conducted 12, 45-minute observations. There were many similarities between the two programs (e.g., both were explicit, systematic, and sequential; both included curriculum-based measures of student learning that informed instruction; both dedicated approximately equal amounts of time to decoding and encoding instruction). However, our observations indicated a statistically significant difference between the programs ( p < .002) in proportion of time dedicated to letter-name knowledge, text reading, and comprehension instruction. The programs also differed in their emphasis on articulating/applying orthographic rules and on particular procedures for decoding and encoding words.